Analisis Motivasi Dan Kedisiplinan Kerja Terhadap Kinerja Karyawan Pada PT XYZ - Ahmad Alfonsus; Sumbogo, Ignatius Ario (UNIVERSITAS KALBIS, 2025)
This study focuses on the influence of motivation (X1) and work discipline (X2) on employee performance at PT. XYZ. The research method used is quantitative, employing numerical data analysis and statistics. A conceptual model is utilized as a diagram depicting the relationships among the factors that affect employee performance. The dependent variable studied is employee performance (Y). The results of the study reveal that motivation has a significant positive influence on employee performance, while work discipline does not have a significant positive influence on employee performance. However, when considered together, motivation and work discipline have a significant impact on employee performance. Based on the research findings, it is recommended for the company to ensure a proper balance between wages and employee performance, encourage measured innovation and risk-taking, effectively manage time and target achievement, and prioritize employee development.